PH-regulated reversible photoluminescence and localized surface plasmon resonances arising from molybdenum oxide quantum dot. (March 2020) - Cao, Haiyan; Hu, Xue; Shi, Wenbing; Li, Siqi; Huang, Yuming
Highlights: A facile strategy was developed to simultaneously tune photoluminescence and visible LSPR of MoOx QDs. As prepared quantum dot acted as an effective dual-modal extreme acidity indicator. The dual-modal sensing platform achieved a high selectivity and excellent reversibility. High feasibility of this probe was confirmed in E. coli cells without influence of background signal. Abstract: Localized surface plasmon resonances (LSPR) and photoluminescence are important for applications of transition-metal oxides. However, simultaneous control of these optical properties is challenging. Here, a facile strategy is presented that simultaneously tunes photoluminescence and visible LSPR of molybdenum oxide quantum dots (MoOx QDs) by controlling lattice vacancies. Specifically, N-doped MoOx QDs were prepared with a one-pot protocol. The introduction of N in MoOx QDs surfaces via ammonia (NH3 ) not only trapped oxygen molecules in the process of forming MoOx QDs, but also provided enough free electrons to enable tunable optical properties. Thus, a MoOx QD-based dual-modal fluorescence and LSPR assay was demonstrated via lattice vacancy concentration tuning. Upon introduction of H + or OH −, pH-reversible tunability of the fluorescence and plasmonic resonance was observed. The dual-mode probe was used to detect extreme acidity in bacterial cells. Overall, tunable LSPR and photoluminescence within one nanostructure via pH-regulation should enable multi-modal signal-outputs for sensing platforms and photoelectric nanodevices.